2018
DOI: 10.1097/md.0000000000011581
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of gabapentin in reducing pain intensity and morphine consumption after breast cancer surgery

Abstract: Background:The purpose of this meta-analysis from randomized controlled trials (RCTs) was to determine the efficacy and safety of the preoperative use of gabapentin for the treatment of acute and chronic postoperative pain following breast cancer surgery.Methods:In November 2017, a systematic computer-based search was conducted in PubMed, Embase, Web of Science, Cochrane Library, and Google databases. RCTs comparing gabapentin with placebo in patients undergoing breast cancer surgery were retrieved. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
1
28
2
Order By: Relevance
“…Two meta‐analyses of parallel group, placebo‐controlled RCTs have evaluated the efficacy of the pre‐operative use of gabapentin for the treatment of acute and chronic postoperative pain following breast cancer surgery . The meta‐analysis by Rai et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta‐analyses of parallel group, placebo‐controlled RCTs have evaluated the efficacy of the pre‐operative use of gabapentin for the treatment of acute and chronic postoperative pain following breast cancer surgery . The meta‐analysis by Rai et al.…”
Section: Resultsmentioning
confidence: 99%
“… included all the studies of the meta‐analysis by Jiang et al. but also included one study concerning gabapentin (516 patients) and four studies concerning pregabalin (209 patients). Doses of gabapentin ranged between 300 mg and 1200 mg. Doses of pregabalin ranged between 150 mg and 900 mg. Gabapentin reduced pain scores in the post‐anaesthetic care unit (PACU) and 24 h postoperatively .…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical study documented that co administration of opioid and GBP provided reduction in opioid use and complications this study also noticed the clinical benefit including critical respiratory failure [66]. Recently, increasing number of clinical reports on efficacy of gabapentin (pre and post-operative) on 'morphine consumption' and in 'reducing pain intensity' have been documented [64][65][66][67][68]. Thus the present study strongly indicated to reveal the functional molecular singling circuits of 'combination of morphine and gabapentin' observed in clinical reports.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic neuropathic pain can be a common problem after surgery, especially in the breast cancer surgery population and those undergoing axillary lymph node dissections. A meta-analysis by Jiang et al [12] aimed to determine the effect of gabapentin on pain control after breast surgery. This review included nine randomized controlled trials that studied women undergoing breast cancer surgery who were randomized to placebo vs. gabapentin.…”
Section: Peri Operative Pain Managementmentioning
confidence: 99%
“…There was significant heterogeneity in pain score outcomes, which they partly contributed to patients undergoing axillary lymph node dissection and the likelihood of more chronic pain development after surgery, which gabapentin is thought to have less of an effect on treatment. They concluded that preoperative use of gabapentin was successful in reducing acute postoperative pain and chronic pain incidence, but encouraged future studies to understand its effect when used postoperatively [12] .…”
Section: Peri Operative Pain Managementmentioning
confidence: 99%